Reverse Radial Artery Flap Perforator Anatomy and Clinical Applications. Issue 3 (September 2016) - White, Colin P.; Steve, Anna K.; Buchel, Edward W.; Hayakawa, Thomas E.; Morris, Steven F.
Abstract : Abstract: The pedicled reverse radial forearm flap is a well-known option for the treatment of a variety of soft tissue wounds including dorsal hand wounds. We document the number, emerging diameter, length from origin, course, and location of all perforators of the radial artery in a series of 6 fresh human cadavers after whole body lead oxide and gelatin injection to confirm and comprehensively document the anatomy of the radial artery perforators. This data provide an anatomic basis for a modification to the reversed radial forearm flap used to decrease venous congestion in the postoperative period. Two case reports are presented to provide clinical demonstration of the importance of this modification.